2015
DOI: 10.1037/xge0000045
|View full text |Cite
|
Sign up to set email alerts
|

Adults are intuitive mind-body dualists.

Abstract: In the present research, we tested the hypotheses that (a) adults are intuitive mind-body dualists, (b) that this belief can be considered a default, and (c) that it is partially explained by essentialistic reasoning about the nature of the mind. Over 8 studies, using various thought experiment paradigms, participants reliably ascribed to a physically duplicated being a greater retention of physical than of mental properties. This difference was unrelated to whether or not this being was given a proper name (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 55 publications
1
80
0
Order By: Relevance
“…If the goals of medicine would be considered in a narrow conception, as not being inclusive of addressing the social roots of disease, then the next step is the risk of getting even narrower, focusing only on bodily disorders and excluding the mental ones, thus leading to accepting the socalled "mental-body dualism" [105] that is an unacceptable assumption in the context of modern bioethics, though 'most adults remain '"essentialistic mind-body dualists" at heart' as Forstmann and Burgmer argue in their study [111]. …”
Section: Otc/ott: Carried Out In a Gray Zone Between Natural And Unnamentioning
confidence: 99%
“…If the goals of medicine would be considered in a narrow conception, as not being inclusive of addressing the social roots of disease, then the next step is the risk of getting even narrower, focusing only on bodily disorders and excluding the mental ones, thus leading to accepting the socalled "mental-body dualism" [105] that is an unacceptable assumption in the context of modern bioethics, though 'most adults remain '"essentialistic mind-body dualists" at heart' as Forstmann and Burgmer argue in their study [111]. …”
Section: Otc/ott: Carried Out In a Gray Zone Between Natural And Unnamentioning
confidence: 99%
“…People have been shown outside the health domain to be inherent dualists, endorsing a separation between physically and mentally based phenomena. 32,33 Applied to health, a single symptom can be judged as to whether it reflects a problem originating from a person’s body (e.g., medical problem) or from a person’s mind (e.g., mental problem). Such medical-mental attributions will not necessarily be accurate 1012 but will nevertheless be influential.…”
mentioning
confidence: 99%
“…Research has demonstrated that we are intuitive dualists, separation being a default strategy [3] [4]. Various thought experiments were employed by Forstmann & Burgmer [3] to assess how we cognitively process the mind and body.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that we are intuitive dualists, separation being a default strategy [3] [4]. Various thought experiments were employed by Forstmann & Burgmer [3] to assess how we cognitively process the mind and body. Physical properties were consistently seen as being retained compared to mental properties, and under conditions that taxed cognitive resources or primed them with an intuitive thinking style, mind-body dualistic beliefs were intensified [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation